FIGURE 8. A–F in Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean ... - In, First Published (Zenodo, 2022)
FIGURE 8. A–F, Moreiradromia antillensis (Stimpson, 1858), scanning electron micrographs of the thoracic sternum. A, B, immature female, cw 5.4 mm (MZUSP 11919). C, D, immature female, cw 8.4 mm (MZUSP 6058). E, F, mature female, cw 8.8 mm (MZUSP 5905). B, D, F, Details of A, C, E, respectively. Note in (A–F) thoracic suture 7/8 extending well beyong the gonopore on the coxa of the third pereopod (CxP3) and continuing to extend forward with growth. The gonopores (A–C) and the spemarthecal openings at the distal end of the thoracic suture 7/8 (B, D, black arrows) are closed in the immature female (A–D) and open in the mature female (E, F, black arrow). In (F) the black arrow also shows the sperm plaque around the spermathecal aperture. Scales: A, C, E, 1 mm. B, D, F, 0.3 mm. ... : Published as part of In, First Published, 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 on page 19, DOI: 10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155 ...